Cytocompatible and Antibacterial Properties of Chitosan-Siloxane Hybrid Spheres - Shirosaki, Yuki (Polymers (Basel), 2019)
Microporous spheres in a hybrid system consisting of chitosan and γ-glycidoxypropyltrimethoxysilane (GPTMS) have advantages in a range of applications, e.g., as vehicles for cell transplantation and soft tissue defect filling materials, because of their excellent cytocompatibility with various cells. In this study, microporous chitosan-GPTMS spheres were prepared by dropping chitosan-GPTMS precursor sols, with or without a cerium chloride, into liquid nitrogen using a syringe pump. The droplets were then freeze dried to give the pores of size 10 to 50 μm. The cell culture tests showed that L929 fibroblast-like cells migrated into the micropores larger than 50 μm in diameter, whereas MG63 osteoblast-like cells proliferated well and covered the granule surfaces. The spheres with cerium chloride showed antibacterial properties against both gram-negative and gram-positive bacteria.